MITOS KUNANG-KUNANG DALAM CERPEN âREQUIEM KUNANGKUNANGâ KARYA AGUS NOOR : ANALISIS SEMIOTIKA - , EKA NURHATIKA PUTRI SEPTIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study entitled âThe Myth of Fireflies In The Short Story âRequiem Kunang-Kunangâ by Agus Noor: studies Semioticsâ is analyzed using the semiotics of Roland Barthes, the Mythology. The reason for choosing Roland Barthes semiotic approach as a tool to analyze a short story âRequiem Kunang- Kunangâ forwarded the symbols in the form of myth. The meaning of the symbols of myth is not obtained with a single readout so that there should be a deeper meaning readings . In addition, the symbol of the myth is a tool used by the author to detail message. In the Mythology , Barthes describes the theory of myth . Myth is a semiology system,the second level of semiology. Myth is a way for delivering a message that serves to distort the meaning of a myth that meant by the myth - makers .Therefore , the theory of Roland Barthes's Mythology is deemed capable of revealing the problems that exist in this study. The results of this study indicate that there are three stories behind the formation of the myth of fireflies as the incarnation of the spirit of a pair of human eyes. The third story is used as the primary marker in the form of short stories depicting the Indonesian government leadership. spirits used as a marker in one of the stories is the meaning of public confidence in Indonesia. After doing a reading deeper meaning, found another marker that refers to the social conflict in Ambon, namely inter-religious conflict. The conflict between religions is a tool that is used by one of the leaders of Indonesia to achieve power. Based on the readings of the deeper meaning, it can be concluded that the three story behind the myth of fireflies with other markers have unified story that culminated with a causal relationship.